Special Issue - July/August 2020: Sustaining a Focus on Human Experience in the Face of COVID-19 - Patient Experience Journal (The Beryl Institute, 2020)
At this critical time in our shared history, we are faced with a powerful challenge, the rapid impact of COVID-19 on our healthcare systems and community. With that acknowledgement, we are refocusing our 2020 special issue of Patient Experience Journal (PXJ) to address Sustaining a Focus on Human Experience in the Face of COVID-19. Submissions received for our initially planned special issue on patient & family experience in behavioral health will remain in review and consideration for future issues of PXJ. There are heroic efforts taking place minute-by-minute to address the clinical and personal needs of patients, while also addressing the physical and emotional needs of those providing and supporting the delivery of care. While the pace of the crisis can be overwhelming and challenging, incredible efforts are underway to manage the intricacies of human need at this time. At its heart, healthcare has been, is and will remain human beings caring for human beings, and in that light significant efforts are taking place, no matter how big or small to address the human experience happening now. Whether addressing the challenges of connection in isolation for patients and families to the burdens of endless and continuous shifts for those providing care, the efforts to ensure not only positive clinical outcomes but also a human experience has never been greater. The moment in which we find ourselves reinforces more than ever that experience is not about survey scores or satisfaction. Rather it is about the efforts we make to acknowledge the person in front of us, to listen, to show dignity and respect, to communicate in ways that are clear and understandable and ultimately to stand with one another. The efforts taking place in healthcare organizations and communities globally represent what is best in humanity, and we invite you to - and hope you will - share your stories here.